Nilai-Nilai Persahabatan dalam Novel 5 Cm Karya Donny Dhirgantoro serta Relevansinya terhadap Bahan Ajar Pembelajaran Sastra di SMA - Aningtyas, Dewi; Israhayu, Eko Sri (Suara Bahasa, 2024)
Literary work is a work of art containing the imagination of the author so as to produce a work that can be felt by connoisseurs of literature. Literary works in the form of novels contain life values such as moral values, social values, educational values, and include the value of friendship to be learned. Therefore, the purpose of this study is to describe the values of friendship in the novel 5 Cm by Donny Dhirgantoro and to find the relevance to the learning of literature in high school. The method used in this research is descriptive qualitative with literary sociology approach. The data source of this research is the novel 5 Cm by Donny Dhirgantoro with a total of 382 pages and the data used are quotes or sentences containing friendship values. The data collection technique used is reading and recording technique by identifying friendship values, collecting data, and making conclusions based on the data that has been obtained. The results of the study show that there is a value of friendship in the novel 5 Cm by Donny Dhirgantoro which consists of the value of mutual understanding, the value of trust, the value of cooperation, the value of loyalty, and the value of honesty. The value of mutual understanding includes several indicators such as mutual understanding, respect, and forgiveness. The value of trust includes indicators of hard work and confidence. The value of cooperation includes indicators of helping each other, reminding each other, and hard work. The value of loyalty includes indicators of caring. Finally, the value of honesty includes indicators of having the courage to admit mistakes and convey something according to the situation.